Conflict intensity in the region of birth increases religiosity among refugees - Frank van Tubergen; Yuliya Kosyakova; Agnieszka Kanas (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
Do violent conflicts increase religiosity? This study draws on evidence from a large-scale survey on refugees in Germany linked with data on time-varying conflict intensity in refugees' birth regions prior to the survey interview. The results show that the greater the number of conflict-induced fatalities in the period before the interview, the more often refugees pray. The relationship between conflict and praying holds equally across demographic subgroups. Evidence suggests that both short- and long-term cumulative fatalities in refugees' birth regions affect how often they pray. Additionally, the link between conflict and praying is stronger for refugees who have family and relatives still living in their country of origin. Finally, we show that the conflicts that matter are those occurring within the refugees' specific region of birth rather than in other regions in the country. Implications for existential insecurity theory and cultural evolutionary theory are discussed.
Keywords: 330; Religiosity; existential insecurity; refugees; praying; war